Gastrointestinal parasite infections and self-medication in wild chimpanzees surviving in degraded forest fragments within an agricultural landscape mosaic in Uganda - McLennan, Matthew R. (PLoS One, 2017)
Monitoring health in wild great apes is integral to their conservation and is especially important where they share habitats with humans, given the potential for zoonotic pathogen exchange. We studied the intestinal parasites of wild chimpanzees (Pan troglodytes schweinfurthii) inhabiting degraded forest fragments amid farmland and villages in Bulindi, Uganda. We first identified protozoan and helminth parasites infecting this population. Sixteen taxa were demonstrated microscopically (9 protozoa, 5 nematodes, 1 cestode, and 1 trematode). DNA sequence analysis enabled more precise identification of larval nematodes (e.g. Oesophagostomum stephanostomum, O. bifurcum, Strongyloides fuelleborni, Necator sp. Type II) and tapeworm proglottids (genus Bertiella). To better understand the ecology of infections, we used multidimensional scaling analysis to reveal general patterns of association among parasites, climate, and whole leaf swallowing–a prevalent self-medicative behaviour at Bulindi linked to control of nodular worms (Oesophagostomum spp.). Prevalence of parasites varied with climate in diverse ways. For example, Oesophagostomum sp. was detected in faeces at higher frequencies with increasing rainfall but was most clearly associated with periods of low temperature. Certain parasites occurred together within chimpanzee hosts more or less frequently than expected by chance. For example, the commensal ciliate Troglodytella abrassarti was negatively associated with Balantidium coli and Oesophagostomum sp., possibly because the latter taxa make the large intestine less suitable for T. abrassarti. Whole leaves in faeces showed independent associations with the prevalence of Oesophagostomum sp., Strongyloides sp., and hookworm by microscopic examination, and with egestion of adult O. stephanostomum by macroscopic inspection. All parasites identified to species or genus have been reported in wild chimpanzees inhabiting less-disturbed environments than Bulindi. Nevertheless, several disease-causing taxa infecting these chimpanzees are potentially transmissible between apes and humans (e.g. rhabditoid and strongyle nematodes), underscoring the importance of identifying and reducing risks of pathogen exchange in shared landscapes.